Teachers’ Pedagogical Competence and Students’ Metacognitive Skills in Islamic Religious Education - Sri Wahyuni; Nurul Hanis Amiruddin Jafry (CV Najmi Edu Creative, 2026)
This study examined the relationship between teachers’ pedagogical competence and students’ metacognitive skills in Islamic Religious Education among eighth-grade students at an Indonesian junior high school. The study used a quantitative correlational design involving 73 students selected through saturated sampling. Data were collected using Likert-scale questionnaires and analysed using normality and linearity tests and simple linear regression in SPSS 22. The findings showed that teachers’ pedagogical competence was categorised as very high (85%), while students’ metacognitive skills were also categorised as very high (82%). Regression analysis demonstrated a significant positive relationship between teachers’ pedagogical competence and students’ metacognitive skills (p < .05). The coefficient of determination (R²) that pedagogical competence explained 43.5% of the variance in students’ metacognitive skills, with the remaining variance attributable to other factors. The findings indicate that stronger pedagogical competence is associated with higher levels of students’ metacognitive skills and reflective learning processes in Islamic Religious Education.